2015
DOI: 10.1002/casp.2229
|View full text |Cite
|
Sign up to set email alerts
|

Can Self‐Determination Theory Explain the Self‐Perpetuation of Social Innovations? A Case Study of Slow Food at the University of Wisconsin—Madison

Abstract: This case study of Slow Food at the University of Wisconsin-Madison (SFUW) examines the success of a volunteer social innovation that promotes sustainable food access. Using inductive thematic analysis of 19 in-depth, semi-structured interviews of past and current members, advisors, and collaborators, we find that the success of SFUW is consistent with Self-Determination Theory. We find that among the participants, the organization satisfies the basic psychological needs for autonomy, competence, and relatedne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Importance, relevance, and clear need The dominant attainment task value as gleaned from the literature is the importance, relevance, and clear need for innovative behavior and goals (Aarikka-Stenroos et al, 2017;Hosseini & Narayanan, 2014). To this end, studies suggested that clear links to desired goals like careers or mastery (Aarikka-Stenroos et al, 2017;Edwards et al, 2014;Sorice & Donlan, 2015;Xie & Reider, 2014) and easy to see logic to how the innovation would be important to society, with a particular emergent theme of social justice and conservation causes (Antikainen & Vaataja, 2010;Reznickova & Zepeda, 2016;Sorice & Donlan, 2015). Leaders seeking to stoke innovation could infer from the literature that making the time to articulate the goals of an innovation and the way that it could benefit workers and society will increase engagement and increase the attainment value of the activity thus propelling the innovating of individuals and teams.…”
Section: Strategies For Building Attainment Valuementioning
confidence: 99%
“…Importance, relevance, and clear need The dominant attainment task value as gleaned from the literature is the importance, relevance, and clear need for innovative behavior and goals (Aarikka-Stenroos et al, 2017;Hosseini & Narayanan, 2014). To this end, studies suggested that clear links to desired goals like careers or mastery (Aarikka-Stenroos et al, 2017;Edwards et al, 2014;Sorice & Donlan, 2015;Xie & Reider, 2014) and easy to see logic to how the innovation would be important to society, with a particular emergent theme of social justice and conservation causes (Antikainen & Vaataja, 2010;Reznickova & Zepeda, 2016;Sorice & Donlan, 2015). Leaders seeking to stoke innovation could infer from the literature that making the time to articulate the goals of an innovation and the way that it could benefit workers and society will increase engagement and increase the attainment value of the activity thus propelling the innovating of individuals and teams.…”
Section: Strategies For Building Attainment Valuementioning
confidence: 99%
“…The literature also distinguishes concepts like "grassroots innovation" (Seyfang & Haxeltine, 2012;Seyfang & Smith, 2007) and "volunteer social innovation" (Reznickova & Zepeda, 2016). The latter article stresses the importance of self-determination for explaining the success of innovation.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…Social innovations may be produced by for-profit organizations (Pol & Ville, 2009), nonprofit organizations (Jaskyte & Dressler, 2005;Perri 6, 1993;Shier & Handy, 2015a, 2015b, government bodies (Osborne & Brown, 2011), or networks of volunteers may have in social innovations. While the literature has linked volunteering to innovation on a conceptual level (Anheier et al, 2014), with broad indicators (Shier & Handy, 2015a) and in case studies (Reznickova & Zepeda, 2016), this study offers a fine-grained analysis on volunteer roles across different organizational contexts. This will help building theory about the unique assets of volunteers in innovative processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It aims at promoting territorial tourism, safeguarding gastronomic heritage and culture and protecting rare local food products [88][89][90], and has activated some tools with the aim of reaching these objectives, e.g., Slow Food presidia [91][92][93][94]. Moreover, some authors used qualitative and quantitative methods to analyzed the phenomenon of Slow Food initiatives e.g., Reznickova and Zepeda [95] gave a inductive thematic analysis supported by semi-structured interviews to the members of Slow Food University of Wisconsin association to investigate into the importance of the Self-Determination Theory; Jung et al [96] carried out an exploratory factor analysis to determine which quality elements of food festivals have a direct impact on the visitors' satisfaction level.…”
Section: Literature Reviewmentioning
confidence: 99%